Environmental and Firm Performance: Evidence from Indonesia - Makhdalena Makhdalena; Desi Zulvina (Universitas Pasundan, 2024)
This study aims to investigate the impact of environmental performance on firm performance in the companies listed on the Indonesia Stock Exchange from 2015 to 2022. Information about a company's environmental responsibility, including resource use, emissions, and innovation, is known as environmental performance. The environmental score from ESG measures environmental performance, and Tobin's Q measures firm performance. The descriptive statistics show that there is an increase in the company's environmental performance every year from 2015 to 2022. The research discovered a positive impact between environmental performance and corporate performance. Research demonstrates firms can improve their financial performance by adopting environmental performance strategies. It underscores the significance of sustainable development for businesses, suggesting that efficient environmental practices enhance financial performance while fostering corporate sustainability. The paper suggests that implementing environmental performance can directly enhance firm performance, leading to improvements in both the environmental and financial aspects of a company. The result offers valuable insights for policymakers and practitioners to improve firm environmental action in order to enhance firm performance, therefore improving transparency between companies and stakeholders.